The implementation of Supply Chain Collaboration in China: Manufacturing Industries - HAN, CHE (2011)
As we know that supply chain management is important to a manufacturing company and Chinese manufacturing companies have great contribution to the world. Unfortunately, Chinese companies still use traditional supply chain to operate, and it will not help companies to improve their performance and save costs. In this way, the topic of this dissertation is investigating one of the modern supply chain management strategies which is supply chain collaboration. In addition, the supplier development is one of the methods of supply chain collaboration, which can assist the implementation of supply chain collaboration. This dissertation aims to explore the drivers and barriers of applying supply chain collaboration, and also examine how to overcome barriers of supply chain collaboration in Chinese companies under current Chinese situations. In order to achieve these objectives, both the empirical data and secondary data are needed to be collected. From the literature review, the researcher found that there were some conflicts between previous authors’ theories about supply chain collaboration and supplier development. The sharing information is the key theme of supply chain collaboration, while not all of researchers agree with that. In addition, implementing supply chain collaboration needs to understand several crucial elements, such as partner selection, advanced information technology, top management support, trust and logistics. These elements will have impact on the successful of implementing supply chain collaboration. At the same time, the successful implementing supplier development also needs to satisfy several conditions, such as top management support, long-term commitment, trust, etc. unfortunately, some Chinese situations cannot satisfy those elements, such as third party logistics, informal channel of communication-Guanxi, and not advanced IT in China. In this way, it seems that applying supply chain collaboration and supplier development are not suitable in Chinese manufacturing companies. In order to get evidences of supply chain collaboration and supplier development, two case studies about Siemens Healthcare and Elekta Ltd are used to be analyzed. According to the data from interviews, the researcher found that supply chain collaboration can reduce inventory, enhance innovation, and improve companies’ products’ quality. While, the underdeveloped IT, adopting 3PL, low openness of information sharing, low trust, difficult to gain top management support, difficult to establish cross-functional teams and low level of staffs coordination are the obstacles of applying supply chain collaboration. In this way, the researcher found the ways to implement supply chain collaboration and supplier development successfully and overcome some of barriers. Firstly, Guanxi, good suppliers’ performance and companies’ good reputation can help companies to obtain trust. Secondly, Chinese companies should choose just a few key suppliers to share information of forecasting and planning with them. Thirdly, the innovation and quality management can be improved by adopting supply chain collaboration. Next, supply chain collaboration can be improved by applying supplier development and information sharing. Last but not least, staffs can show the benefits of improvement of suppliers’ performance to gain top management support. In this way, the objectives of this dissertation can be reached by empirical data and secondary data. Key words: supply chain management, supply chain collaboration, supplier development, drivers, barriers, implementation, and information sharing.